PENINGKATAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM SISWA SMK NEGERI 3 RAHA MELALUI PEMBELAJARAN MODEL STUDENT TEAMS ACHIEVEMENT DEVISION (STAD) - aminah, aminah (IAI Al-Mawaddah Warrahmah Kolaka, 2020)
Islamic Religious Education is one of the compulsory subjects that must be taught at every level of education in Indonesia. Therefore, subject teachers are required to be more creative in compiling teaching materials and determining suitable learning models and attracting students' attention in receiving lessons in class. This needs to be done because suitable teaching materials and methods will affect the learning process and outcomes of students. One of the learning models that can be used in teaching Islamic Religious Education is the cooperative model of the Student Teams Achievement Devision (STAD) type. This learning model emphasizes students to take an active role in learning, both in groups and independently. Classroom Action Research was carried out on students of the Boutique Clothing Department Class XI Clothing 1 at SMK Negeri 3 Raha in the 2019/2020 academic year with the subject matter focused on the procedures for organizing corpses with basic competence in implementing body management in accordance with the provisions of Islamic law. The results showed that the learning outcomes of students in the Boutique Clothing Department of Class XI Clothing 1 at SMK Negeri 3 Raha through the Student Team Achievement Divisions (STAD) type of cooperative learning model increased. The percentage of completeness of students in cycle I was 68.77%, cycle II was 80.29%.